Structure-Function Relations in Oxaloacetate Decarboxylase Complex. Fluorescence and Infrared Approaches to Monitor Oxomalonate and Na+ Binding Effect - Granjon, Thierry; Maniti, Ofelia; Auchli, Yolanda; Dahinden, Pius; Buchet, René; Marcillat, Olivier; Dimroth, Peter (PLOS ONE, 2010)
Background Oxaloacetate decarboxylase (OAD) is a member of the Na+ transport decarboxylase enzyme family found exclusively in anaerobic bacteria. OAD of Vibrio cholerae catalyses a key step in citrate fermentation, converting the chemical energy of the decarboxylation reaction into an electrochemical gradient of Na+ ions across the membrane, which drives endergonic membrane reactions such as ATP synthesis, transport and motility. OAD is a membrane-bound enzyme composed of α, β and γ subunits. The α subunit contains the carboxyltransferase catalytic site. Methodology/Principal Findings In this report, spectroscopic techniques were used to probe oxomalonate (a competitive inhibitor of OAD with respect to oxaloacetate) and Na+ effects on the enzyme tryptophan environment and on the secondary structure of the OAD complex, as well as the importance of each subunit in the catalytic mechanism. An intrinsic fluorescence approach, Red Edge Excitation Shift (REES), indicated that solvent molecule mobility in the vicinity of OAD tryptophans was more restricted in the presence of oxomalonate. It also demonstrated that, although the structure of OAD is sensitive to the presence of NaCl, oxomalonate was able to bind to the enzyme even in the absence of Na+. REES changes due to oxomalonate binding were also observed with the αγ and α subunits. Infrared spectra showed that OAD, αγ and α subunits have a main component band centered between 1655 and 1650 cm−1 characteristic of a high content of α helix structures. Addition of oxomalonate induced a shift of the amide-I band of OAD toward higher wavenumbers, interpreted as a slight decrease of β sheet structures and a concomitant increase of α helix structures. Oxomalonate binding to αγand α subunits also provoked secondary structure variations, but these effects were negligible compared to OAD complex. Conclusion Oxomalonate binding affects the tryptophan environment of the carboxyltransferase subunit, whereas Na+ alters the tryptophan environment of the β subunit, consistent with the function of these subunits within the enzyme complex. Formation of a complex between OAD and its substrates elicits structural changes in the α-helical as well as β-strand secondary structure elements.